Implementasi Prinsip Prinsip Pelayanan Publik - Adistya Shofia Finanda; Jihan Fira Fadhila; Hayat Hayat (Universitas Warmadewa, 2024)
Quality public services are at the core of effective and responsive governance. This article discusses the key principles that form the foundation for good public service and their relevance in the current context of public administration. The principles of public service include accessibility, equity, affordability, prompt response, accountability, and user satisfaction. Accessibility ensures that public services are available and accessible to all without discrimination. Equality emphasizes the importance of treating all citizens fairly and without prejudice. Affordability means that public services should be affordable for all levels of society, regardless of economic status. Prompt response is key to meeting people's needs and expectations efficiently and effectively. Accountability ensures that service providers are accountable for their actions to the public and have mechanisms to receive feedback and criticism. User satisfaction becomes the main measure in evaluating the quality of public services. The implementation of public service principles requires a strong commitment from the government to prioritize the needs and interests of the community. Through sustained efforts to improve the quality and accessibility of public services, governments can strengthen their legitimacy, build public trust, and create a positive impact in the lives of citizens.